Prenatal detection of uniparental disomy of chromosome 2 carrying a CHRND pathogenic variant that causes lethal multiple pterygium syndrome. Issue 6 (5th February 2018) - Shen, W.; Young, B.A.; Bosworth, M.; Wright, K.E.; Lamb, A.N.; Ji, Y.
Abstract :